PENGARUH MODAL PSIKOLOGI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA DIMEDIASI OLEH KEPUASAN KERJA - Nur Zaman; Endang Tjahjaningsih (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
The purpose of the researh is for analyzing an influence of psychological capital and organizational citizenship behavior, studies at Family Planning Educator of Village in Office of Women Empowerment and Family Planning, Batang District, Central Java Province. The research belongs to purposive sampling method it is for every people that have period about 5 to 20 years in their work. There are 133 people, and just 115 persons as the sample. Measurement of the instrument response by using likert scale 7 (seven) as an alternative of the respond. The instrument of the test by using validity and reliability test, model test by using determination coefficient and F test (Goodness of Fit). The hypotesis test is in the research by using t test with frequency distribution to significance level (α) 5%. The result showed several changes from the variable of psychological capital, organizational citizenship behavior (OCB) and job satisfaction can be done by Family Planning Founder of Village performance in the model. The result of hipotesis test showed that the psychological capital and OCB have a positif influence and significant to the performance of employees, thus satisfaction job can mediate psychological and OCB to ward Family Planning Educator of Village in Office of Women Empowerment and Family Planning performance, but direct influence was stronger. Keywords : Psychological capital, OCB, Job Satisfaction and Performance